A study on Responsible Behavioural Practices for Sustainable Development of Tourism in Mysore - Soonthodu, Sachin; Singh, Sumit Kumar (Turizam, 2024)
Responsible practices intend to establish a positive relationship between the destination and the stakeholders of tourism. These actors include the local community, tourists, local businessmen, employees, authorities, government, and non-government organizations. While tourists play a vital role in the sustainable development of a destination, the local community largely remains the beneficiary as well as the victim of the consequences of impacts caused by tourism activities. Hence, the growth of the local community must happen sustainably. Mysore, the heritage city of Karnataka, was recently recognized as one of the cleanest cities in India. However, tourism activities adversely affect the sustainable practices of the city. The study highlights that insufficient supportive services and a lack of responsible behavioural practices among tourists are the challenges to the sustainable development of tourist attractions in various attractions of Mysore.